Clinical and radiological outcomes with PEEK suture anchors used in rotator cuff repair: our experience confirm that a perianchor fluid signal on RM does not affect clinical outcome at one year of follow up - Di Benedetto, Paolo; Gorasso, Giovanni; Beltrame, Alessandro; Mancuso, Francesco; Buttironi, Michele Mario; Causero, Araldo (Acta Biomedica Atenei Parmensis, 2020)
Introduction / objectives Osteolytic-type reactions of the perianchor bone which in magnetic resonance are manifested as hyperintensity of the signal in T2 images are reported in many studies. T  The objective of the present study is to evaluate and compare to the literature data the clinical and radiological results of a group of patients who underwent arthroscopic suture of a rotator cuff tear using polyetherketone (PEEK) suture anchors.Materials and methodsTwenty patients, aged between 44 and 73 years, who underwent arthroscopic repair of the rotator cuff for lesions smaller than 4 cm considered reparaible between August 2017 and January 2019, were enrolled in the present study. Patients were evaluated clinically with clinical examination, Constant scale and ASES scale pre and post surgery. MRI either pre and post operation at one year were evaluated to obtain data about tendon healing and evaluate bone reaction to PEEK anchors.Results:MRI analysis showed a tendon signal according to Sugaya classification of type 1 in the 25% of patients, type 2 in the 60% of cases and type 3 in the remaining 15% . Osteolysis was grade 0 in 65%, grade 1 in 30 % and grade 2 in 5% of cases. No anchors pull out or mobilization were reported.Conclusions:The presence of a T2 hyperintense signal osteolysis like on MRI control using PEEK anchors for the sutur of rotator cuff lesions does not find correlation whit the final clinical result of the procedure.